The Direction of the Federal Supreme Court in The Interpretation of Constitutional Texts: Analytical Applied Study - Othman Yaseen Ali (QALAAI ZANIST JOURNAL, 2020)
The Federal Supreme Court in Iraq is the competent body that exercises judicial censorship over constitutional laws and regulations in force and the interpretation of constitutional texts, in accordance with paragraphs first and second of Article (93) of the 2005 constitution, In this research is entitled (The direction of the Federal Supreme Court in the interpretation of constitutional texts) and is an analytical applied study, we examined through three sections on the direction of the Federal Court of Iraq in the interpretation of the provisions of the Iraqi Constitution of 2005, The first topic dealt with the importance of interpretation of the texts of the law and its doctrines and methods, In Second topic, we discussed the jurisdiction of the Federal Supreme Court in the interpretation, In the Third topic which is last section we devoted it to the statement of the expansionist trend and the restricted approach of the Fedral court in the interpretation of the constitutional texts. In conclusion, we mentioned to the most important conclusions we reached through this research, and also we made several recommendations, to activate the role of the Federal Supreme Court in Iraq to solve the problems, and accurate interpretation of constitutional texts.